Handling of Culture-Specific Terms in Translation - Kitanovska-Kimovska, Sonja & Silvana Neshkovska (Универзитет „Гоце Делчев“ – Штип (Македонија) и Воронешки државен универзитет (Русија), 2018)
The aim of this paper is to make an in-depth analysis of the translation strategies used in transposing culture specific terms from Oscar Wilde’s play - “The Importance of Being Earnest” - into its Macedonian translation, “Vazno da si Bogumil”, by Dragi Mihajlovski. More precisely, the paper seeks to ascertain what culture specific terms have been used in the source text and whether the culture specific terms used in the translation belong to the same domains as those from the source text. It also seeks to determine what translation strategy is most frequently utilized, and whether the overall tendency is more towards ‘domesticating’ or ‘foreignising’ the translated text. The findings indicate that the culture specific terms used in the translation do not always belong to the same domains as those used in the original. Furthermore, the most prevalent strategy employed by the translator was adaptation which means replacing the culture specific terms from the original text with culture specific terms typical of the target language and culture.
Keywords: translation, culture-specific terms, strategies